Facile synthesis of poly(Safranine T)/Reduced graphene oxide nanocomposite for supercapacitors with wide potential window in aqueous neutral electrolyte. Issue 4 (2nd April 2016) - Yang, Yu Jun
ABSTRACT: A facile method is introduced for incorporating reduced graphene oxide (rGO) into poly(safranine T) (PST) films. First, ST-functionalized GO (ST/GO) was obtained via the absorption of ST on GO in pH 7.0 phosphate buffer solution. Then rGO/PST composite was synthesized by the electropolymerization of ST and the subsequent electrochemical reduction of GO. The as-prepared PST/rGO composite films are characterized using scanning electron microscope, X-ray diffraction, and Fourier transform–infrared spectroscopy. PST/rGO composites possess a microporous structure, which creates enormous amount of pores, and therefore provides larger interfaces for charge carrier. The properties of electrochemical capacitance for PST/rGO composites have also been investigated with cyclic voltammetry (CV) and galvanostatic charge–discharge measurements. The experimental results manifest that the PST/rGO composite showed high capacitance (293.2 F g −1 ) at 20-mV s −1 CV scan and an excellent cycling stability (8.3% drop after 1000 cycles) in 0.1 M Na2 SO4 electrolyte.